The ionospheric signature of transient dayside reconnection and the associated pulsed convection return flow - S. E. Milan (Annales Geophysicae, 1999)
Three SuperDARN coherent HF radars are employed to investigate the excitation of convection in the dayside high-latitude ionosphere in response to transient reconnection occurring in the cusp region. This study demonstrates the existence of transient antisunward-propagating backscatter features at the expected location of the ionospheric footprint of the cusp region, which have a repetition rate near 10 min. These are interpreted as the ionospheric signature of flux transfer events. Moreover, transient sunward-propagating regions of backscatter are observed in the convection return flow regions of both the pre- and post-noon sectors. These patches are observed to propagate towards the noon sector from at least as far around the auroral zone as 07 MLT in the pre-noon sector and 17 MLT in the post-noon sector, travelling with a velocity of approximately 1.5 to 2 km s-1. These return flow patches have a repetition rate similar to that of the transient features observed at local noon. While providing supporting evidence for the impulsive nature of convection flow, the observation of sunward-propagating features in the return flow region is not consistent with current conceptual models of the excitation of convection. Key words. Ionosphere (plasma convection) · Magnetospheric physics (magnetopause · cusp · and boundary layers; magnetosphere-ionosphere interactions)